Video dermoscopy study of the skin - Isaieva, O. A.; Аврунін, О. Г. (Liverpool, United Kingdom., 2019)
The work is devoted to the study of the main pathologies of the skin, the possibility of diagnosing them using video dermatoscopy. Determining the differences between digital dermoscopy and video dermoscopy. The difference between the diagnosis of common skin diseases from malignant and tumors is considered. The science of fluorescent technology is being studied. The diagnostic capabilities of digital dermatoscopy are discussed.
Keywords: skin features; video dermatoscopy; skin diagnostics; melanoma; skin pathologies